برصغیر میں فتاویٰ جات کا رجحان اور اثر و نفوذ ؛ ایک تجزیاتی مطالعہ ) فتاو ی رضویہ ازامام احمد رضا خان بریلوی کا خصوصی مطالعہ (: The trend & influence of fatwas in the subcontinent; An analytical study (A Special Study of Fatawa Rizviyya by Imam Ahmed Raza Khan Barelvi) - Bano, Dr. Ruqia; Rafique, Dr. Sumayyah (Al-Amīr Research Journal for Islamic Studies, 2023)
Before the arrival of the British in the Indian subcontinent, there was an environment of an Islamic state, which had its own problems that were a reflection of the Islamic state, but after the arrival of the British, Muslims had to face some new problems that were a reflection of the English civilization and culture. It was important to know the solution of these problems in the context of Islamic Sharia, therefore, along with other Islamic books, fatwas were also written in this period, but it would not be right to say that as many fatwas were written in this period as never before Not done Fatawa Rizwiyyah holds a prominent position in these Fatawas ۔This article provides an introduction to Imam Ahmad Raza Khan Barelvi, highlighting his influential role within the South Asian Sunni Barelvi movement during the late 19th and early 20th centuries. It then introduces the "Fatawa Razawiyya," discussing its style, methodology, and significance 6specific criteria and arguments Imam Ahmad Raza Khan used in issuing decrees of kufr (infidelity) against various groups he considered heretical, such as the Qadianis and Natureis, during his time. This analysis is critical in understanding the dynamics of religious orthodoxy and the boundaries of acceptable belief within the context of Barelvi thought and the broader Sunni community. The study draws upon a range of doctrinal sources, historical contexts, and theological debates, making it a valuable contribution to the studies of Islamic law and intra-faith relations. Keywords: Imam Ahmad Raza Khan Barelvi, Fatawa Razawiyya, Takfir Methodology,Islamic Jurisprudence, Sunni Barelvi Movement, Heresy, Orthodoxy, Religious Decrees,Qadianis, Natureis, Intra-faith Relations.